Another Piece of the Job Creation Puzzle : Developing the MSME Sector in Egypt - Nasr, Sahar; Abdelkader, Laila (World Bank, Washington, DC, 2013)
The Egyptian revolution resulted in key challenges but also opportunities. It has highlighted the need for more jobs, a level playing field, good governance (transparency and accountability), as well as a fair and competitive environment to accelerate inclusive growth. It is essential to address the challenges the country faces and build on the opportunities at this historical time. Micro, Small and Medium Enterprises (MSMEs) are the main source of private sector jobs in Egypt and in the MENA region as a whole. A recent World Bank analysis of 99 countries shows that firms with less than a hundred employees account for the lion's share of employment creation.